Testing: a systemic functional view of high stakes test preparation materials - Schulze, Joshua (Colombian Applied Linguistics Journal, 2009)
Educators of English language learners (ELLs) frequently use test preparation materials to help ELLs prepare for high stakes language exams. This study uses tools of systemic functional linguistics (SFL) to examine how academic language is used to construct meaning within these test preparation materials. While the test preparation materials and available test excerpts contain a range of genres, this study focuses particularly on informational texts with scientific topics, designed for upper elementary students. The results highlight pedagogical advantages of using SFL to develop genre awareness in ELLs by attending to the linguistic features evident in the genre.